PENGARUH LKS BERBASIS INKUIRI TERBIMBING DISERTAI PERMAINAN ULAR TANGGA TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMA DI KABUPATEN JEMBER - Intan Widi Prasetyawati; Subiki Subiki; Aris Singgih Budiarso (FKIP Universitas Jember, 2019)
Abstract Student worksheet based on the guided inquiry with the snakes and ladders game is one of innovation teaching materials that is used as an alternative learning in the class .This study aims to knowing the the influence of students worksheet based on the guided inquiry with the snakes and ladders game towards student motivation dan learning outcomes .This study research is an experimental research with a population of all students in a class of xi mipa senior high schools 4 jember , and the sample used is students of class XI MIPA 1 and XI MIPA 3.The result of this study shows that after implementing learning using LKS based on guided inquiry with the snakes and ladders game the average of student motivation and learning outcomes reaches 80,44% and 91,29, this result shows that a student motivated to learn after and their learning outcomes increase. Keywords : worksheet guided inquiry, motivation, learning outcomes, snake and ladders game